Do contextual factors, tournament level, and location affect external match load in elite Brazilian youth soccer players? - Rites, A.; Viana, D.; Merino-Munoz, P.; Miarka, B.; Aedo-Munoz, E.; Perez-Contreras, J.; Pinto Salerno, V. (Journal of Physical Education and Sport, 2022)
The present study compares the external load of a Brazilian first-division U-20 team match between the tournament level (regional vs. national) and the match's location (home or away). Methods: Thirty-five athletes from a U-20 team belonging to the same Brazilian first-division team participated in the study (age=19.1 ± 0.58 years; body mass=70.1 ±7.64 kg; height=176.1 ±6.28 cm). Twenty-eight games belonging to the national championship (14 Brasileirão matches) and regional championship (14 Carioca state matches) were analyzed, following these external load variables through a global positioning system: total distance traveled (TD), player load (PL), distance traveled >20 km/h, distance traveled >25km/h, the number of accelerations and decelerations> 2 m/s2 (AD2) and >3 m/s2 (AD3) and the number of Repeat High-Intensity Efforts (RHIE). A two-factor ANOVA compared the tournament level and the match`s location, and the effect size (ES) was verified, considering p=0.05. Results: Significant differences were found in TD (F=3.42 and ES=0.7), PL (F=4.2 and ES=0.8), D20 (F=2.87 and ES=0.67), AD3 (F=6.49 and ES=0.97), RHIE (F=14.6 and ES=1.18) and in AD2 (F=10.1 and ES=1.24). No effects were found according to location or interaction effects (p>0.1). Conclusion: Findings indicated that the tournament type impacts the external match load - with higher effort values in the national tournament. The location did not affect the external load, but further studies are required to corroborate these results due to the lack of public presence because of the COVID-19 pandemic. The following data may be helpful for the coaching staff to consider this factor when planning and programming the training load concerning the tournament in which they are participating.